(untitled) (Journal of Atomic and Molecular Sciences, 2021)
A more general algebraic expression for the calculation of the four-mode Franck-Condon factors was derived straightforwardly on the basis of the closed form expression of the Franck-Condon integrals between arbitrary multidimensional harmonic oscillators under the Duschinsky mixing effects. This new algebraic expression was applied to study the photoelectron spectra of D_2CO^+(A ^2B_1). Franck-Condon analyses and spectral simulations were carried out on the D_2CO^+(A ^2B_1)-D_2CO(X ^1A_1) photoionization processes. The spectral simulations of vibrational structures based on the computed Franck-Condon factors are in excellent agreement with the observed spectra.